DAMPAK STIGMA YANG DIALAMI PETUGAS KESEHATAN SELAMA PANDEMI COVID-19: REVIEW LITERATUR [THE IMPACT OF STIGMA EXPERIENCED BY HEALTH WORKERS DURING THE COVID-19 PANDEMIC: LITERATURE REVIEW] - Pasaribu, Jesika; Keliat, Budi Anna; Daulima, Novy Helena Chatarina; Hastono, Sutanto Priyo (Nursing Current: Jurnal Keperawatan, 2023)
The COVID-19 pandemic has affected the mental health of health workers. The pandemic situation has affected health workers physically and mentally. Inadequate knowledge about COVID-19 and fear of new diseases have the potential to cause stigma. Health workers exposed to COVID-19 while carrying out their duties are also stigmatized. This article aims to identify the stigma experienced by health workers due to COVID-19. EBSCO and ProQuest electronic database searches used search terms and found 10 articles that met the inclusion criteria. Two themes were found: the causes of stigma and the impact of stigma on health workers. The results of the review found that the stigma experienced had an impact on the mental health condition of health workers and affected the quality of professional work. It is imperative to undertake initiatives aimed at mitigating the stigma experienced by healthcare professionals in order to uphold their mental well-being and ensure their sustained professional performance. BAHASA INDONESIA Pandemi COVID-19 telah memengaruhi kesehatan mental tenaga kesehatan. Situasi pandemi telah memengaruhi kondisi petugas kesehatan secara fisik dan mental. Pengetahuan tentang COVID-19 yang belum memadai dan ketakutan terhadap penyakit baru berpotensi menimbulkan stigma. Petugas kesehatan yang terpapar COVID-19 dalam menjalankan tugas turut mendapatkan stigma. Tujuan artikel ini adalah untuk mengidentifikasi bagaimana stigma yang dialami petugas kesehatan akibat COVID-19. Pencarian database elektronik EBSCO dan ProQuest dilakukan dengan menggunakan istilah pencarian dan di temukan 10 artikel yang sesuaidengankriterianinklusi. Ditemukan dua tema dalamyaknipenyebab stigma dan dampak stigma padapetugaskesehatan. Hasil telaah menemukan stigma yang dialami berdampak pada penurunan kondisi kesehatan mental petugas kesehatan dan memengaruhi kualitas kerja profesional. Upaya menurunkan stigma padapetugas kesehatan perlu dilakukan agar kesehatan mental petugas kesehatan tetap terjaga dan tetap dapat bekerja secara profesional.